Pendampingan Pemasaran Gula Aren Menggunakan Media Sosial Instagram di Desa Ujung Tebu Kabupaten Serang - Dwi Nurina Pitasari; Martha Lena; Felycia (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Ujung Tebu village has abundant natural resource potential, especially the main ingredient for making palm sugar. The problem faced by the community as partners is the decline in palm sugar sales due to low public knowledge in marketing techniques using social media so that palm sugar products are only marketed in the surrounding environment. The purpose of this activity is to provide assistance to the community, especially palm sugar entrepreneurs regarding interesting marketing techniques using social media, especially Instagram. The method used goes through several stages, namely the first delivery of material to the community as participants, then the second stage is the assistance in creating Instagram accounts and marketing techniques. The result of this activity is the desire of the palm sugar entrepreneur community to market palm sugar using Instagram social media so that it is easier to sell and can increase their income and marketing outside the region